Deciphering the mechanism of jujube vinegar on hyperlipoidemia through gut microbiome based on 16S rRNA, BugBase analysis, and the stamp analysis of KEEG - Duan, Guofeng; Li, Lijuan (Frontiers in Nutrition, 2023)
Background Growing data indicate that the gut microbiome may contribute to the rising incidence of hyperlipoidemia. Jujube vinegar lowers lipids, protects the liver, and reduces oxidant capacity, however, it is unknown whether this is due to the gut flora. To further research the role of the gut microbiome in treating hyperlipidemia with jujube vinegar, we looked into whether the action of jujube vinegar is related to the regulation of the gut microbiome. Method Thirty male ICR mice were used. The control group (CON), the high-fat diet (HFD) group, and the vinegar group (VIN) each consisted of ten female ICR mice fed consistently for eight weeks. For each treatment, we kept track of body mass, liver index, blood lipid levels, and oxidative stress state. We also analyzed mouse feces using high-throughput 16srRNA sequencing to examine the relationship between jujube vinegar’s hypolipidemic effect and antioxidant activity and how it affects the gut microbiome. Results Jujube vinegar reduced body weight by 19.92%, serum TC, TG, and LDL-C by 25.09%, 26.83%, and 11.66%, and increased HDL-C by 1.44 times, serum AST and ALT decreased by 26.36% and 34.87% respectively, the blood levels of SOD and GSH-Px increased 1.35-fold and 1.60-fold, respectively. While blood MDA decreased 33.21%, the liver’s SOD and GSH-Px increased 1.32-fold and 1.60-fold, respectively, and the liver’s MDA decreased 48.96% in HFD mice. The gut microbiome analysis revealed that jujube vinegar increased the intestinal microbial ASV count by 13.46%, and the F/B (Firmicutes/Bacteroidota) ratio by 2.08-fold in high-fat diet mice, and the proportion was significantly inversely correlated with TC, TG, and LDL-C and positively correlated with HDL-C. Biomarker bacteria in the vinegar group included Lactobacillaceae and Lactobacillus, which correlated favorably with HDL-C, SOD, and GSH-Px and negatively with LDL-C, TC, and TG. Jujube vinegar increased the abundance of the Aerobic, Contains Mobile Elements, and Facultative Aerobic by 2.84 times, 1.45 times, and 2.40 times, while decreased the abundance of Potential pathogens by 44.72%, according to the BugBase study. The KEGG analysis showed that jujube vinegar was predominantly reflected in the biological process of gene function and related to signal transduction pathways, including glucagon signaling system, HIF-1 signaling pathway, adipocytokine signaling pathway, amino sugar, and nucleotide sugar metabolism, and so forth. Conclusion Based on these findings, jujube vinegar may reduce hyperlipoidemia by controlling the gut microbiome and enhancing antioxidant capacity.